The effect of fiscal loss compensation, capital intensity and company age on tax avoidance - Silvera, Cut Putri; Ismanto, Juli (WIM Solusi Prima, 2024)
Tax avoidance is a strategy and technique carried out by taxpayers safely because it does not violate tax provisions. This technique usually takes advantage of loopholes (grey areas) in tax regulations to reduce the amount of tax to be paid. The government does not like tax avoidance because it directly reduces state revenues. This study aims to determine the effect of fiscal loss compensation, capital intensity, and company age on tax avoidance. Secondary data comes from the financial statements of companies included in the Consumer Non-Cyclicals Sub-Sector Food and Beverage index listed on the IDX during the 2019-2023 period. A total of 14 companies were used as research samples for five years. Panel data regression analysis was used in this study. The results showed that fiscal loss compensation and capital intensity did not have a significant effect on tax avoidance. Conversely, company age has a significant effect on tax avoidance. This shows that company age can indirectly affect tax avoidance. Older companies tend to reduce costs including their tax costs because of the experience and learning they have and the influence of other companies in the same or different industries. Companies that operate longer also become more adept at managing their taxes based on previous experience. Logically, the longer a company operates, the more experience it has so that the human resources it has become more adept at managing and administering tax burdens, which ultimately increases the tendency to engage in tax avoidance.